Prevalence and diversity of avian blood parasites in a resident northern passerine - Van Hemert, Caroline (Parasit Vectors, 2019)
BACKGROUND: Climate-related changes are expected to influence the prevalence and distribution of vector-borne haemosporidian parasites at northern latitudes, although baseline information about resident birds is still lacking. In this study, we investigated prevalence and genetic diversity of Plasmodium, Haemoproteus, and Leucocytozoon parasites infecting the northwestern crow (Corvus caurinus), a non-migratory passerine with unique life-history characteristics. This species occupies both intertidal and forested habitats and is subject to high prevalence of avian keratin disorder (AKD), a disease that causes gross beak deformities. Investigation of avian blood parasites in northwestern crows at sites broadly distributed across coastal Alaska provided an opportunity to evaluate specific host factors related to parasite infection status and assess geographical patterns of prevalence. RESULTS: We used molecular methods to screen for haemosporidian parasites in northwestern crows and estimated genus-specific parasite prevalence with occupancy modeling that accounts for imperfect detection of parasite infection. We observed considerable geographical and annual variation in prevalence of Plasmodium, Haemoproteus, and Leucocytozoon, but these patterns were not correlated with indices of local climatic conditions. Our models also did not provide support for relationships between the probability of parasite infection and body condition or the occurrence of co-infections with other parasite genera or clinical signs of AKD. In our phylogenetic analyses, we identified multiple lineages of each parasite genus, with Leucocytozoon showing greater diversity than Plasmodium or Haemoproteus. CONCLUSIONS: Results from this study expand our knowledge about the prevalence and diversity of avian blood parasites in northern resident birds as well as corvids worldwide. We detected all three genera of avian haemosporidians in northwestern crows in Alaska, although only Leucocytozoon occurred at all sites in both years. Given the strong geographical and annual variation in parasite prevalence and apparent lack of correlation with climatic variables, it appears that there are other key factors responsible for driving transmission dynamics in this region. Thus, caution is warranted when using standard climatic or geographical attributes in a predictive framework. Our phylogenetic results demonstrate lower host specificity for some lineages of Leucocytozoon than is typically reported and provide insights about genetic diversity of local haemosporidian parasites in Alaska. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-019-3545-1) contains supplementary material, which is available to authorized users.